2012
DOI: 10.1002/elps.201100471
|View full text |Cite
|
Sign up to set email alerts
|

Statistical properties of the electrophoretic collision of a long DNA molecule with a small obstacle

Abstract: We present experimental results for the collision of a single λ-DNA molecule with isolated cylindrical nanoposts whose radii range from 350 nm to 1.37 μm. The experimental apparatus was fabricated in oxidized silicon using a plasma-thinning method. The probability density for the dimensionless holdup time is described by a gamma distribution, which accurately represents the behavior of the probability density for X collisions and U/J collisions for short-lived and long-lived collisions, respectively. The shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…At this dye ratio, YOYO-1 bisintercalation into the DNA backbone saturates and external binding to the DNA molecule begins [21]. We have found that a relatively high dye ratio is useful for high spatial and temporal resolution of single molecules based on our previous work [18,22]. While such a high dye ratio was not necessary for data acquisition in the 5-reservoir device, we used a constant dye ratio for both the single molecule and the ensemble level experiments to facilitate comparison between them.…”
Section: A Single Molecule Experiments In a 2-reservoir Devicementioning
confidence: 80%
See 3 more Smart Citations
“…At this dye ratio, YOYO-1 bisintercalation into the DNA backbone saturates and external binding to the DNA molecule begins [21]. We have found that a relatively high dye ratio is useful for high spatial and temporal resolution of single molecules based on our previous work [18,22]. While such a high dye ratio was not necessary for data acquisition in the 5-reservoir device, we used a constant dye ratio for both the single molecule and the ensemble level experiments to facilitate comparison between them.…”
Section: A Single Molecule Experiments In a 2-reservoir Devicementioning
confidence: 80%
“…Neutral, adsorbed polymers suppress electroosmotic flow (EOF) during electrophoresis by forming a dynamic surface coating [23]. While several polymers have been shown to reduce EOF in capillaries [24], we chose PVP based on its success in microfluidic devices [1,5,6,14,18,20,22,25,26]. The device can be conditioned with the polymer overnight to develop a uniform surface coating [22,27,28]; however, several groups have had success conditioning the device for less than one minute [24], or simply including polymer in the running buffer [6,14,20,25,26].…”
Section: A Single Molecule Experiments In a 2-reservoir Devicementioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Doyle and Dorfman formulated new models describing polymer-obstacle collisions based on single molecule data. [46][47][48][49][50] Nanoconfinement Polymer chains in confined geometries have been observed to adopt similar conformations to polymer chains in strong extensional flows. 51 Polymer confinement is typically described using three variables: channel dimension d, polymer persistence length p, and polymer radius of gyration R g .…”
mentioning
confidence: 99%